تقييم جودة الخدمات الصحية في المؤسسات الاستشفائية الخاصة من وجهة نظر الزبون - العباسي, رمزي (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2021)
الملخص: تهدف هذه الدراسة إلى التعرف على مستوى جودة الخدمات الصحية المقدمة من طرف المؤسسات الاستشفائية الخاصة - بولاية عنابة – من وجهة نظر الزبون، وذلك من خلال الإشكالية التالية: "ما مدى رضا المرضى عن جودة الخدمات الصحية المقدمة من طرف المؤسسات الاستشفائية الخاصة- بولاية عنابة"؟، ومن أجل معالجة هذه الإشكالية تم تصميم استبانة لجمع المعلومات وتوزيعها على عينة الدراسة المكونة من (400) زبون (مريض) على مستوى (05) مؤسسات استشفائية خاصة بولاية عنابة ومعالجتها احصائيا بالاعتماد على برنامج "الحزمة الإحصائية للعلوم الاجتماعية SPSS" نسخة (26) وبرنامج "MINITAB " نسخة (16)، لمعرفة تقييم المرضى لجودة الخدمات الصحية المقدمة لهم، بالإضافة إلى معرفة فيما إذا كان هناك اختلاف في تقييمهم لأبعاد جودة الخدمة الصحية تعود للعوامل الديمغرافية والشخصية. توصلت الدراسة إلى جملة من النتائج العملية من أبرزها: وجود رضا من طرف المرضى على جودة الخدمات الصحية المقدمة لهم في المؤسسات الاستشفائية الخاصة - بولاية عنابة – عند مستوى معنوية (0.05)، وكذلك عدم وجود فوارق ذات دلالة إحصائية بين اتجاهات المرضى في تقييمهم لأبعاد جودة الخدمات الصحية المقدمة في المؤسسات الاستشفائية الخاصة بولاية عنابة تعزى للخصائص الديمغرافية والشخصية. وتوصي الدراسة على ضوء النتائج المتحصل عليها إلى ضرورة التفاعل مع آراء ومقترحات الزبون (المريض) ووضع نظام فعال للاستماع للزبون وتلقي الشكاوى، والعمل على تطوير الوحدات الإدارية التي تعنى بالجودة داخل المؤسسات الاستشفائية الخاصة ومنح استقلالية وصلاحيات واسعة لها، وكذا التعاون مع مخابر البحث التابعة للمؤسسات الجامعية للاستفادة من جموع الباحثين المختصين سواء في مجال الإدارة الصحية أو مختلف المجالات ذات الصلة، والاستفادة من البرامج التدريبية والمشاركة بالملتقيات العلمية المتخصصة، إضافة إلى توفير الأجهزة والمعدات الحديثة التي تتماشى والتطور التكنولوجي المتسارع وتحديث صالات وردهات المرضى وأماكن الاستقبال ومكاتب الطاقم العامل بالمؤسسات وتوسيعها. Résumé : فرنسية أو انجلزية This study aims to identify the level of quality of health services provided by private hospital institutions - in Annaba - from the customer's point of view, through the following research question: "How satisfied are patients with the quality of health services provided by private hospital institutions – in the state of Annaba"? In order to address this problem, a questionnaire was designed to collect information and distribute it to the study sample consisting of (400) clients (patients) from (05) private hospitals in Annaba, and address it statistically depending on the "Statistical Package for Social Sciences" version (26) and "MINITAB version (16), in order to know the patients' evaluation of the quality of the health services provided to them, in addition to knowing whether there is a difference between their evaluations of the dimensions of health service quality based on demographic and personal factors. The study reached a number of results, the most prominent of which are: the satisfaction of patients with the quality of health services provided to them in private hospital institutions - in the state of Annaba - at a significant level (0.05). In addition, there are no statistically significant differences between patients’ attitudes in evaluating the dimensions of the quality of health services provided in hospital institutions in the state of Annaba based on demographic and personal factors. The study recommends, based on the results obtained, the necessity of interacting with the opinions and suggestions of the client (the patient) and establishing an effective system to listen to the customer and receive complaints, and work to develop administrative units concerned with improving service quality within private hospital institutions and accord them autonomy and broad powers, as well as cooperating with research laboratories of university institutions to benefit from the masses of specialized researchers, whether in the field of health administration or various areas of concern, and benefit from training programs and participate in specialized scientific forums, in addition to providing modern devices and equipment in keeping with the rapid technological development, modernizing and expanding patients’ lounges and lobbies, reception areas and employees’ offices.
- دراسة حالة عينة من المؤسسات بولاية عنابة-
أطروحة دكتوراهتخصص: أطروحة دكتوراه في علوم التسيير تخصص إدارة أعمال في العلوم الاقتصادية و التسيير
Keywords: الخدمة الصحية، جودة الخدمة الصحية، أبعاد جودة الخدمة الصحية، المؤسسات الاستشفائية الخاصة، رضا الزبون; Health service, Quality of health service, Dimensions of health service quality, Private hospital institutions, Customer satisfaction.